فاعلية الذات وعلاقتها بجودة الأداء لدى أساتذة مرحلة التعليم الابتدائي - شرون, عفاف (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة باللغة العربية: هدفت الدراسة الحالية إلى الكشف عن طبيعة العلاقة بين فاعلية الذات وجودة الأداء لدى أساتذة مرحلة التعليم الابتدائي ببلدية سيدي عمران، كما هدفت أيضا إلى الكشف عن دلالة الفروق لدى عينة الدراسة في فاعلية الذات وجودة الأداء تبعا لمتغير (عدد سنوات العمل)، باستخدام المنهج الوصفي الإرتباطي وتم تطبيق الدراسة على عينة قوامها (50) أستاذا وأستاذة تم اختيارهم بالطريقة العشوائية البسيطة من بين المؤسسات التعليمية ببلدية سيدي عمران ولاية المغير، باستخدام مقياس فاعلية الذات الذي أعده مسعودي (2016) ومقياس جودة الأداء (لبدرخان) والذي تم إدخال فيه بعض التعديلات، وبعد إعادة التأكد من الخصائص السيكومترية للمقياسين وجمع وتحليل البيانات باستخدام معامل الارتباط بيرسون وتحليل التباين الأحادي لدراسة الفروق توصلت الدراسة إلى النتائج التالية: - توجد علاقة طردية متوسطة ذات دلالة إحصائية بين درجات فاعلية الذات وجودة الأداء لدى أساتذة مرحلة التعليم الابتدائي ببلدية سيدي عمران عينة الدراسة. - لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات فاعلية الذات لدى أساتذة مرحلة التعليم الابتدائي عينة الدراسة تعزى لمتغير عدد سنوات العمل(أقل من 5 سنوات/من 6 إلى 10 سنوات/ أكثر من 10 سنوات). - لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات جودة الأداء لدى أساتذة مرحلة التعليم الابتدائي عينة الدراسة تعزى لمتغير عدد سنوات العمل(أقل من 5 سنوات/من 6 إلى 10 سنوات/ أكثر من 10 سنوات). وعلى ضوء نتائج الدراسة والإرث النظري حول الموضوع خلص البحث إلى مجموعة من التوصيات أهمها: - إجراء دراسات لاحقة تبحث في فاعلية الذات وعلاقتها بجودة الأداء لدى المعلمين وفق متغيرات أخرى كالمؤهل العلمي والمراحل التعليمية والجنس. - العمل على توفير مقاييس للكشفعلى جودة أداء للمعلمين، والاهتمام بتنمية مستوى جودة الأداء لديهم. Abstract: The current study aims to reveal the nature of the relationship between self-efficacy and performance quality among primary education teachers in Sidiamrane municipality, and also aimed to reveal the significance of the differences in the study sample in self-efficacy and performance quality depending on the variable (number of years of work), using the descriptive associative approach and the study was applied to a sample of (50) professors and professors selected in a simple random way from among the educational institutions in Sidiamrane municipality, El Meghaier state, using the self-efficacy scale prepared by Messaoudi (2016) and the performance quality scale (badarkhan) in which some modifications were made, after re-checking the psychometric characteristics For the two scales and the collection and analysis of data using Pearson correlation coefficient and unilateral variance analysis to study the differences the study reached the following results: -There is an average direct relationship with statistical significance between the grades of self-efficacy and the quality of performance among primary school teachers in the municipality of Sidiamran sample of the study. -There are no statistically significant differences between the average self-efficacy scores of primary school teachers in the study sample due to the variable number of years of work(less than 5 years/from 6 to 10 years/ more than 10 years). -There are no statistically significant differences between the averages of the performance quality scores of the primary education teachers of the study sample attributed to the variable number of years of work(less than 5 years/from 6 to 10 years/ more than 10 years). In light of the results of the study and the theoretical legacy on the subject, the research concluded a set of recommendations, the most important of which are: - Conducting subsequent studies looking at self-efficacy and its relationship to the quality of performance among teachers according to other variables such as educational qualification, educational stages and gender. -Work on providing measures to detect the quality of performance for teachers,and pay attention to the development of the level of performance quality for them.
دراسة ميدانية ببعض ابتدائيات بلدية سيدي عمران ولاية المغير
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: فاعلية الذات، l'auto-efficacité, self-efficacy; جودة أداء المعلم، qualité de la performance des enseignants, quality of teacher performance